Genetic dissection of maternal influence on in vivo haploid induction in maize - CGIAR Research Program on Maize (2021)
The optimized method showed on average 5.6 times higher overall success rate (OSR) compared to the standard haploid seedling immersion method which was the second-best method in our experiments.